Asymmetrical fatiguing of the gluteus maximus muscles in the elite short-track female skaters - Mariusz Konieczny; Paweł Pakosz; Mateusz Witkowski (BMC, 2020)
Abstract Background According to research, fast skating on short distances increases functional asymmetry of leg muscles. As has been proven in many sporting disciplines, this asymmetry can increase the risk of injury. The aim of the study was to analyze the level of right and left myolectrical manifestations of fatigue asymmetry of gluteus maximus muscle in elite skaters on a short track and to compare this phenomenon to a control group. The muscles were chosen deliberately, due to their influence in maintaining the right position during training on ice. Methods The experiment compared a group of eight members of the Polish Women's National Team in short track with a group of eight non-training people. The subjects did the Biering-Sorensen test, in which sEMG (surface electromyography) signal frequency was measured in the gluteus maximus muscles during an isometric contraction. Myolectrical manifestations of fatigue slopes were analyzed with a ANOVA with repeated measures. In the skaters, the myolectrical manifestations of fatigue differed between the right and the left gluteus maximus muscles. All the skaters had higher myolectrical manifestations of fatigue in the right leg. This phenomenon was not observed in the non-training subjects, who on average had similar myolectrical manifestations of fatigue in both legs. Results Results showed that the right and the left muscles of the skaters in the experimental group differed in myolectrical manifestations of fatigue, but this difference was non-significant in the control group. The subjects from the two groups did not differ in the myolectrical manifestations of fatigue of the left muscle, they did in the myolectrical manifestations of fatigue of the right muscle. The elite speed-track skaters had higher myolectrical manifestations of fatigue in the right muscle than the non-training subjects. Conclusions Training should thus be planned in a way that minimizes the risk of causing muscle myolectrical manifestations of fatigue asymmetry in skaters despite the typically asymmetrical muscle work during training on ice and competition, thus new training protocols should be developed or considered to decrease that asymmetry. Trial registration The tests were previously approved by the Bioethical Commission of the Chamber of Physicians in Opole. (Resolution No. 235 of 13 December 2016).